Development of a Prototype System for Monitoring and Controlling Cat Care Based on the Internet of Things - Rahmawati, Yosy; Zuchriadi, Achmad; Wahyudyan, Dzidan Wiladnurrizqi (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2025)
In today's fast-paced and stressful daily life, many people experience fatigue and stress, necessitating solutions to alleviate these feelings. Taking care of pets, especially cats, can have a positive impact on human mental health. However, caring for cats requires time and effort, particularly in monitoring their health and the environmental conditions of their living space. This study aims to design and develop a prototype of a cat care monitoring and control system based on the Internet of Things (IoT), enabling real-time monitoring and automated control of various aspects, including cat health, body temperature, and feeding. The system integrates multiple components, including ESP-32, MLX90614 GY-906 Sensor, Ultrasonic Sensor, DHT11 Sensor, RTC DS1302, Servo Motor, Relay, LCD 16x2, 5V Water Pump, Exhaust Fan, and the Telegram application as a monitoring interface. The study's findings indicate that air-conditioned rooms provide the most stable and comfortable temperature and humidity conditions for both pets and humans. Additionally, the DHT11 sensor is more suitable for indoor humidity measurement, whereas the DTH sensor is more optimal for outdoor environments. The ultrasonic sensor proves to be practical for distance measurement, while the load cell delivers precise results for weight measurement requiring high accuracy and stability. This research offers an innovative solution to enhance cat monitoring and care, contributing to an overall improvement in pet quality of life.